2011
DOI: 10.1016/j.ijge.2011.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and Cognitive Impairment: Kahrizak Elderly Study

Abstract: Keywords: cognitive impairment, diastolic high blood pressure, elderly, systolic high blood pressure s u m m a r y Background: Dementia is a major cause of cognitive impairment in the elderly. Numerous studies have investigated the association between hypertension and cognitive disorders in elderly persons, with inconsistent results. The goal of the study was to investigate the association between hypertension at baseline and cognitive impairment after 24 months' follow-up in the elderly residents of the Kahri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 27 publications
3
22
2
Order By: Relevance
“…Our findings of variables predicting an association with cognitive impairment build upon previous work among older adults (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). In this study, self-reported hypertension was not a significant predictor of cognitive impairment.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Our findings of variables predicting an association with cognitive impairment build upon previous work among older adults (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). In this study, self-reported hypertension was not a significant predictor of cognitive impairment.…”
Section: Discussionsupporting
confidence: 84%
“…In this study, self-reported hypertension was not a significant predictor of cognitive impairment. The literature reports conflicting results regarding the influence of hypertension and gender on cognitive impairment (29,(43)(44)(45). Gender, though significant in bivariate analysis, was not found to be an independent predictor in this study when the other variables were introduced in the regression model.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Besides this, in Iran as well the risk of dementia due to hypertension remains modest (1.4 times, 95% CI 1.0–2.2) [27]. Just like elsewhere, the risk of dementia in MENA may also depend upon the type of hypertension (systolic or diastolic) and whether it is controlled or not [53]. …”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that smoking might be a risk factor for the development of dementia 19,20 . Several other studies have suggested that smoking improves cognitive performance 21 .…”
Section: Discussionmentioning
confidence: 99%